Characteristics regarding the consumer of giant squid from Baja California Sur, Mexico - Montaño Méndez, Iliana Enriqueta; Hernández González, Luis Alberto; Lomelí Mayoral, Hiram; Mesías Díaz, Francisco Javier; Ávila Arce, Adanelly (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
The catch of the giant squid (Dosidicus gigas), represents de second fishing activity most important in volume in Baja California Sur, Mexico; is an essential specie not only at the state level but at the pacific and even the national level.Mexico occupies in the world the eight level in the production of squid, but the national consumption, even though the low price of the product and the high nutritional level, is approximately 0.53 kg per year, very low compared to countries like Japan, Korea and Spain (average consumption per capita is of 3.5 kg). In this context, the objective of this article is to caracterize the sudcalifornia consumer preference; determine the buying habits and the consumption; and also to establish the market areas of the squid in Baja California Sur, which allows the introduction of actions for its commercialization, in order to strengthen the market of this product and its general activity. This is why in 2012 a questioner of 1066 consumers was distribute around the five counties of the state, according to the population density. The results indicate that the principal motive why there is not consumption is the difficulty to find places where to buy it, together with the problems of cooking it. Also, it can be seen the high level of ignorance the consumer has regarding the nutritional level this food has. For this reason, future strategies for the commercialization must be focus on better distribution and new form of presenting this product which facilitates its preparation and consumption, and at the same time create campaign which increase awareness of the nutrition level this product has.